An Epizootiological Report of the Re‐emergence and Spread of a Lineage of Virulent Newcastle Disease Virus into Eastern Europe. Issue 3 (15th December 2015) - Fuller, C.; Löndt, B.; Dimitrov, K. M.; Lewis, N.; van Boheemen, S.; Fouchier, R.; Coven, F.; Goujgoulova, G.; Haddas, R.; Brown, I.
Summary: A number of contemporary outbreaks of Newcastle disease (ND) in Israel, Turkey, Georgia and Bulgaria have all been caused by a very similar viruses related to lineage 5a (genotype VIIa). Comparison with published ND virus (NDV) sequences suggests that this virus strain originated in South‐East Asia and on introduction has circulated widely in backyard poultry in the Middle East and into Eastern Europe. An intracerebral pathogenicity index of 1.9 was obtained for a representative isolate from Bulgaria. In addition, the International Reference Laboratory for ND has characterized a molecular epidemiologically linked virus that has been reported to have caused disease in well‐vaccinated broiler chickens in Pakistan. In the 1990s, another strain from the 5a lineage NDV was introduced into Europe and spread across the continent causing numerous outbreaks up to 1999. Despite improved controls, including good diagnostic tests and widespread vaccination, in commercial poultry, the novel circulating NDV strains described here have been established widely in the region and represent an increased risk for similar disease outbreak events to reoccur within the EU.